Exploring the Relationships Between Democracy and Central Bank Independence - Setiadi, Bara (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
This paper applies fixed-effect panel regression on observational data from both developed and developing countries to test the established models of the impact of democracy, political rights, civil liberties, and political institutions on central bank independence (CBI). Evidence shows that lower civil liberties and political risk statistically influence CBI in both developed and developing countries. The findings also show that well-exercised democracy and political rights significantly influence CBI in developing countries only. By contrast, most political variables do not significantly influence CBI in highly developed countries. Instead, CBI depends on macroeconomic variables such as higher taxes and international debt. These findings provide new insights that differ from previously established results, which predict that CBI is not sensitive to political variables. Overall, this paper reaffirms the interplay between politics (proxied by democratic practices) and economy (proxied by CBI) in the early stages of development which varies across different levels of development.